Pendidikan Sosial Berbasis Tauhid dalam Perspektif Al-Qur'an - Muhammad Khoiruddin (Aplikasia, 2018)
The perspectives of Quran to make a statement on also in education social and the paradigms of sosio-humanis teosentris, it is by descriptional quran the relation between a man with god (habl min allâh) and man and man (habl ma’a al-nâs), which are generally what it suggests that there are two issues that need to among the various relevant parties in the practice of in the Islamic education, promised to supply as many dimensions of dialectics horizontally and dimension their desire of submission vertical. In dimension dialectics horizontally, also in education social and evidence of the oneness based should be able to develop the reality of the life of, both the clean water that those concerning with the wide by him my back, the community, as well as the universe with accounts of all all that is in it , while in dimension their desire of submission some more excellent than the vertical that education called social and evidence of the oneness based in addition to providing a an instrument for charged with the care of, capitalize on the fact that , and preserve natural resources, also i desire that can become a bridge to understand phenomena and honeybee in their effort to attain intercourse life to the creator.